Probing the Q-Proton pathway of ba3-cytochrome c oxidase by time-resolved fourier transform infrared spectroscopy - Soulimane, Tewfik; Varotsis, Constantinos; Koutsoupakis, Constantinos (My University, 2004)
In cytochrome c oxidase, the terminal respiratory enzyme, electron transfers are strongly coupled to proton movements within the enzyme. Two proton pathways (K and D) containing water molecules and hydrophobic amino acids have been identified and suggested to be involved in the proton translocation from the mitochondrial matrix or the bacterial cytoplasm into the active site. In addition to the K and D proton pathways, a third proton pathway (Q) has been identified only in ba3-cytochrome c oxidase from Thermus thermophilus, and consists of residues that are highly conserved in all structurally known heme-copper oxidases. The Q pathway starts from the cytoplasmic side of the membrane and leads through the axial heme a3ligand His-384 to the propionate of the heme a3 pyrrol ring A, and then via Asn-366 and Asp-372 to the water pool. We have applied FTIR and time-resolved step-scan Fourier transform infrared (TRS2-FTIR) spectroscopies to investigate the protonation/ deprotonation events in the Q-proton pathway at ambient temperature. The photolysis of CO from heme a 3 and its transient binding to CuBis dynamically linked to structural changes that can be tentatively attributed to ring A propionate of heme a3 (1695/ 1708 cm-1) and to deprotonation of Asp-372 (1726 cm-1). The implications of these results with respect to the role of the ring A propionate of heme a3-Asp372-H 2O site as a proton carrier to the exit/output proton channel (H 2O pool) that is conserved among all structurally known heme-copper oxidases, and is part of the Q-proton pathway in ba3-cytochrome c oxidase, are discussed
Keywords: Bacteria; Cytochrome oxidase; Fourier transform infrared spectroscopy; Amino acids; Heme; Copper; Enzymes; Protons